LINGUISTIC PROBLEMS OF TRANSLATING ARTISTIC WORKS FROM UZBEK TO ENGLISH AS AN EXAMPLE OF THE NOVEL "ULUGBEK TREASURE" BY ODIL YAKUBOV - Nilufar Rukhillayeva; Iroda Jurayeva Ahmedovna (Scholars Digest Publishing, 2024)
This article discusses the analysis of linguistic and grammatical transformations in the translation from Uzbek to English of "Ulugbek's Treasure" by Odil Yaqubov, one of the masterpieces of Uzbek literature.
Keywords: translation, artistic translation, orthographic transformation, punctuation transformation, lexicological transformation, morphological transformation, syntactic transformation.